The Southern Voice: Zapatista and the Challenge towards Neoliberal Agenda in a Globalized World - Gultom, Yosua Saut Marulitua; Andara, Namira Naza; Hutauruk, Muhammad David Ferdian (Institute of International Studies, 2025)
The Zapatistas, emerging in the early 1990s in Chiapas, Mexico, advocate for indigenous autonomy, participatory democracy, and social justice, offering a powerful critique of neoliberal globalization. Their decentralized governance model, based on autonomous municipalities known as